Role of Post Offices in Remittances and Financial Inclusion - Clotteau, Nils (World Bank, Washington, DC, 2012)
Historically post offices have played a role in the provision of remittances and basic financial services to low-income populations. As this function is being revived in an increasing number of developing and emerging countries, remittance services can be improved to better match financial inclusion goals. This paper describes the efforts being made in Sub-Saharan Africa to increase access to remittance services through post offices in small towns and rural areas, and discusses how this improved access could be used to develop crucial savings and other financial services for the poor. The outcomes are encouraging, though a number of constraints must be removed to fully realize the potential of posts in this area.